Prevalence of Narcotics Abuse and their Complications in Pregnant Women Referring to the Obstetric Department of Valiasr Hospital, Birjand - Seyyed Alireza Saadatjoo (فصلنامه دانشگاه علوم پزشکی جهرم, 2011)
Introduction:Nowadays, substance abuse has crossed many social, economic and geographical boundaries, presenting itself as a major health challenge. It affects many demographic groups, including pregnant women, rendering them susceptible to maternal and fetal complications. The aim of the present study is to investigate the prevalence of narcotics abuse in pregnant women, as well as the ensuing maternal and fetal outcomes.Material and Methods:This is a descriptive-analytic study conducted on all pregnant women referring to the obstetric department from October 2006 to December 2007. Data were collected using questionnaires, and analyzed with SPSS software.Results:The prevalence of addiction was 0.69% in women admitted for delivery. The mean age of addicted women was 29.4 ± 1.32 years and the most frequent age subgroup (45.5%) pertained to ages 20-29 years. In the women studied, we found 11.4% placental abruption, 10% stillbirth, and 37.6% fetal distress. The mean gestational age was 34.6 ± 1.34 weeks, with addicted women having a significantly higher prevalence of premature delivery (p≤0.01). The odds ratio (OR) for premature delivery was 5.96 times higher for addicted women.Conclusion:Despite the small number of pregnant addicts, they constitute a high-risk population in terms of perinatal outcomes. Therefore, the educational programs during pregnancy must focus on rehabilitation or substitution of narcotics with safer drugs.